Evaluating nurses’ knowledge regarding dosage calculation at Civil Hospital, Karachi - Mangrio, Abdul Rahim; Jokhio, Pir Bux; Mahar, Saif Ullah (International Journal of Endorsing Health Science Research, 2020)
Background: Appropriate therapeutic care and management is primarily based on the knowledge of dosage calculation and associated skills. The objective of this study was to determine the awareness of staff nurses working in a tertiary care hospital regarding the dose calculation. Methodology: A pre-and post-test interventional study was conducted at a Civil Hospital, Karachi over a sample of 50 staff nurses working in different departments. The data was collected using an assessment tool containing 20 items to evaluate the drug dosage calculation skills and knowledge of the staff nurses. The assessment test was taken once initially after enrollment and then an extensive interventional training regarding the dosage calculation was provided to each nurse which was followed by a post intervention assessment test. The results were then rated on the basis of knowledge scores both before and after intervention i.e. 1-5 (poor), 6-10 (satisfactory), 11-15 (good) and 16-20 (excellent). Data was analyzed using SPSS Version 21.0. Results: A total of 50 nurses participated in this study, of which 44% were males and 56% were females. The nurses had better knowledge both pre & post-test regarding the intravenous medication as compared to the oral for e.g. the nurses of neurosurgery department obtained a mean pre-test score of 4.2±0.8 (oral) and 10.1±2.4 (Intravenous), while the mean post -test were 4.7±0.7 (oral) and 14.6±0.7 (Intravenous). Another point of concern was the dosage calculation in pediatrics department was compromised both for oral and intravenous 2.8±1.7 (pre-oral) and 6.5±1.2 (post-intravenous) increased to 4.6±0.7(post-oral) and 13.6±1.8 (post-intravenous). Moreover, 18% of nurses had poor knowledge of dosage calculation as rated on the pre-test assessment while based on the post-test score none of the nurses had poor knowledge, majority was labeled as having improved knowledge of dosage calculation after interventional training. Conclusion: Overall, the study reveals that the majority of the staff nurses lack adequate knowledge and skills related to drug dosage calculations. There is a dire need for in-service education to enhance the knowledge and skills of staff nurses related to drug dosage calculations.